On Two-stage Logarithmically Asymptotically Optimal Testing of Multiple Hypotheses Concerning Distributions from the Pair of Families - Haroutunian, Evgueni; Hakobyan, Parandzem; Hormozi nejad, Farshin (Mathematical Problems of Computer Science, 2021)
Two-stage testing of multiple hypotheses for a model with two given families of hypothetical probability distributions is considered. The matrix of reliabilities of logarithmically asymptotically optimal hypotheses testing by a pair of stages is studied and compared with the case of similar one-stage testing.